Universal, yet local: The religious factor in Chinese Muslims' perception of world developmental hierarchy. (October 2016) - Lai, Qing; Mu, Zheng
Since its introduction in the late 19th century, developmental thinking has quickly diffused throughout Chinese society. Nowadays, Chinese people extensively employ the concept of development to understand different countries in hierarchical order. Using survey data collected in Gansu, China, we confirmed the nearly universal existence of such developmental worldviews. Overall, our respondents' perceptions conformed to the United Nations' developmental hierarchy based on the Human Development Index scores. However, local Muslims tended to deviate slightly more than other Chinese from the UN standard. This does not mean that Chinese Muslims were reluctant to adopt developmental thinking. In fact, in their eyes, developmental ideas have been prominently associated with Islam since the beginning of the 20th century. Our analysis shows that the observed Muslim–Han disparity is entirely due to Muslims' higher evaluations of development in countries with strongly Islamic populations – in this case, Pakistan. Other than this religion-based disparity, Gansu Muslims and local Han Chinese do not differ in their perceptions of the world developmental hierarchy.